Co-benefits of the National Key Ecological Function Areas in China for carbon sequestration and environmental quality - Chen, Hanyu; Hou, Mengyang; Xi, Zenglei; Zhang, Xiao; Yao, Shunbo (Frontiers in Ecology and Evolution, 2023)
The National Key Ecological Functional Areas (NKEFAs) are a location-oriented ecological engineering of China, which rely on the main functional area planning. This paper is designed to assess the co-benefits of ecological product supply and ecological environment improvement in NKEFAs. On this basis, the establishment of NKEFAs is considered a quasi-natural experiment, and the impact of NKEFAs on carbon sequestration (CS) and environmental quality (EQ) is assessed using a time-varying difference-in-differences (DID) model based on the panel data of prefecture-level cities in China from 2001 to 2019. Additionally, we explore whether the co-benefits of ecological product supply and eco-environment protection can be achieved. The results indicate that NKEFAs enhance CS and EQ and thus achieve co-benefits for both. NKEFAs can influence the co-benefits through territory spatial allocation and labor force aggregation, but industrial structure upgrading only positively mediates the impact of NKEFAs on CS. The co-benefits of NKEFAs are heterogeneous on CS and EQ across functional area types, geospatial locations, and quantiles, while only CS at windbreak-sand fixation area, northwestern region, and low quantile regions is enhanced. This study makes a theoretical and methodological contribution to the existing literature on the policy effect assessment of ecological engineering. It also provides a comprehensive framework for evaluating the effects of relevant policies in other countries by integrating the co-benefits of ecological products and eco-environment, analyzing regional heterogeneity, and exploring the underlying mechanisms.